Some of Hematclogical and Biochemical Parameters of Children Infected with Anemia in Samawa City - Resan Ibraheem, Ihsan (University of Thi-Qar Journal of Science, 2019)
Anemia spreads a widely in many countries in the world particularly the poor and developing countries . Iraq is one of these countries and many of children suffer from bad environmental health , and economic conditions . Samples of blood collected from patients infected with anemia in the hospital of children and delivery in samawah city . Hematological and biochemical parameters were determined , hematological parameters included packed cell volume , hemoglobin concentration , total white blood cells count while biochemical parameters included glucose , cholesterol , billrubin and urea concentrations were measured . Results showed High significant increase (P<0.01) in the number of children infected with iron deficiency anemia in comparison with other types of anemia , so number of children infected with sickle cell anemia and hemolytic anemia . Also there was high significant decrease (p<0.01) in hemoglobin concentration and packed cell volume in all types of anemia in comparison with a control group Glucose and bilirubin increased significantly (p<0.01). Total white blood count increased significantly (p<0.01) in patients with thallasemia . sickle cell anemia and hemolytic anemia compared with patients with iron deficiency anemia and a control group . Total serum cholesterol high significant decreased (p<0.01) in all types of anemia compared with a control group . Results showed there were non significant differences in urea levels in all types of anemia compared with a control group.